Curriculum Management for Interdisciplinary Integration in Islamic Junior High Schools: A Case Study of Madrasah Tsanawiyah - Hilma Fauzia Ulfa; Mulyawan Safwandy Nugraha (Mazidah: Journal Of Educational Research, 2025)
The integration of religious and general knowledge is a fundamental principle of Islamic education, but the curriculum practices in madrasah tsanawiyah (junior high school) still show disciplinary separation, which results in fragmented learning and weak integration of student competencies. This study aims to analyze the implementation of interdisciplinary curriculum management at MTs Al-Mishbah in Bandung and identify obstacles to teacher adaptation from the perspective of Islamic Education Management. The research used a qualitative approach with a case study design. Data collection was conducted through in-depth interviews with the deputy head of the madrasah in charge of the curriculum, general subject teachers, and religious subject teachers, observation of the teaching and learning process in the classroom, and analysis of curriculum documents in the form of syllabi and lesson plans. The data were analyzed using thematic analysis techniques to find patterns and implementative meanings. The results of the study indicate that the madrasah curriculum has not been systematically integrated. The integration of disciplines is only applied to certain materials, is not supported by integrated syllabi and assessment instruments, there is minimal collaboration between teachers, and there are constraints in terms of competence, time, and managerial support. This study emphasizes that an interdisciplinary curriculum in madrasahs requires strengthening the functions of planning, organizing, and developing human resources as the core of Islamic Education Management.